2016
DOI: 10.1016/j.jsha.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width and neutrophil-to-lymphocyte ratio predict left ventricular dysfunction in acute anterior ST-segment elevation myocardial infarction

Abstract: Increased RDW and NLR on admission, in anterior STEMI patients treated with primary PCI are associated with LV systolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 36 publications
2
27
0
1
Order By: Relevance
“…The neutrophil-to-lymphocyte ratio (NLR), determined as the ratio of absolute neutrophil count to lymphocyte count, is a novel inflammatory biomarker used as a prognostic factor in various diseases [24]. It has been previously studied [25][26][27][28], but in light of the racial and ethnic differences found in NLR [29], more studies examining these relationships in different populations should be conducted. Although several studies have investigated the effect of dietary patterns, anthropometric measurements, or metabolic parameters on inflammatory markers, studies using the NLR as an inflammation indicator are not common.…”
Section: Introductionmentioning
confidence: 99%
“…The neutrophil-to-lymphocyte ratio (NLR), determined as the ratio of absolute neutrophil count to lymphocyte count, is a novel inflammatory biomarker used as a prognostic factor in various diseases [24]. It has been previously studied [25][26][27][28], but in light of the racial and ethnic differences found in NLR [29], more studies examining these relationships in different populations should be conducted. Although several studies have investigated the effect of dietary patterns, anthropometric measurements, or metabolic parameters on inflammatory markers, studies using the NLR as an inflammation indicator are not common.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the predictive performance of these biomarkers on the outcomes was limited. More recently, several efficient biomarkers, including gamma-glutamyl transferase (GGT) [25,26], GGT-to-platelet ratio (GPR) [27], mean platelet volume (MPV) [28,29], red blood cell distribution width (RDW) [30,31], and monocyte-to-HDL-C ratio [32], emerged. ALT, mainly derived from the liver, was considered as a marker of liver function.…”
Section: Discussionmentioning
confidence: 99%
“…21 karakaset al, divided patientsinto two groups according to LVEF and there RDW (red cell distribution width) and NLR were assessed at time of admission.Group 1 (systolic dysfunction, LVEF<50%) and Group 2 (preserved global systolic function, LVEF>50%), concludes that mean RDW and NLR were significantly higher in group 1 patients. 22 Zhang et al demonstrated that hemoglobin, neutrophil/ lymphocyte ratio (NLR), Global Registry of Acute Coronary Event score, and post procedure left ventricular ejection fraction (LVEF) were independent predictors of MACEs. 23 But Abrel et al concluded that high NLR was independently associated with lower ejection fraction (49+8 vs 46+8; P<0.001) and fewer hospital complications.…”
Section: Discussionmentioning
confidence: 99%